Role of Conflict and Role Handling Style on Work Performance in Selected private Organizations in Dhaka - Syed Sirrul Mowla, Sadrul Huda (2016)
This thesis attempts to explore the nature, dimensions, management and implications of organizational conflict in the context of service sector of Bangladesh. This is an exploratory research. The research pursued the post-positivist approach, followed the stratified random sampling method. The sample size was 347. The research instruments were structured questionnaire for survey and discussion check list for in-depth interview. The results were presented in both descriptive and inferential form. Percentage analysis, simple regression analysis, t-test, and Anova method were used for data analysis. The results found that role conflict was most prevalent form of conflict followed by interpersonal conflict and group level conflict in service sector. The impact of these conflicts on organizational performance was also examined and it was found that these conflicts had both positive and negative consequence for organizations. Interestingly, results showed that the group level conflict had the most significant impact on employees work performance and the impact was positive. Compromise out of five conflict management styles, was used most frequently followed by accommodate. The research also found that the use of compromise and accommodate techniques were positively related with work performance. The thesis found that male employees preferred more compete style, whereas female employees preferred compromise. No statistically significant variation of conflict was found in respect to employees selected personal (e.g. age, income) and professional variables (management hierarchy, nature of organization). The thesis concludes with observation that more research on different dimensions of organizational conflict in different other industries need to be carried on to have an in-depth understanding of the issue. So that organizations can better equip to handle the organizational conflict for smooth attainment organizational objectives.